The Phenomenon of the Independent Curriculum in Developing Gross Motor Skills in Early Childhood at TK Swasta Jahari Stabat - Mariati, Sri; Rozana, Salma (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
This study examines the implementation of the Independent Curriculum in developing gross motor skills among early childhood learners at TK Swasta Jahari Stabat. Gross motor skills, which involve coordinated body movements using large muscles, are crucial for children's physical and cognitive development. Using a qualitative research method, data were collected through interviews, observations, and documentation with school administrators and teachers. The findings reveal that the Independent Curriculum facilitates active, play-based learning, allowing children to develop motor skills through creative activities such as walking on balance beams, zigzag running, and crawling through obstacles. Compared to the previous curriculum, this approach provides greater flexibility for teachers to design engaging activities suited to children's needs. These results support prior research on the benefits of activity-based learning in early childhood education. The study concludes that the Independent Curriculum significantly enhances gross motor skill development. Future research should explore long-term impacts and additional strategies for optimizing early childhood physical education.